Improving student midwives' workplace learning by moving from self- to co-regulated learning!. Issue 3 (June 2019) - Embo, M.; Valcke, M.
Abstract: Background: Contemporary perspectives on regulated learning are moving beyond models, emphasising individual learning (self-regulated learning) to models that position social transactions at the core of learning (co-regulated learning). In discussing this paradigm shift, it is important to study self- and co-regulated learning in situational context but research in the context of midwifery education is scarce. Objective: This study aimed to improve our understanding of regulating midwifery students' learning by exploring factors that promote or inhibit the capacity to independently self-regulate learning during internships. Design: We conducted a qualitative study involving semi-structured group discussions with final year undergraduate midwifery students (Belgium). Focus groups were audio-taped, transcribed verbatim and analysed in a thematic way. Findings: The majority of respondents did not experience an education intended to stimulate continuous self-regulated learning. They identified many social transactions (with mentors, teachers, teams of midwives, students, peer students, personal environments, personal coaches and curriculum managers) that were instrumental in promoting or inhibiting the ability to independently self-regulate. Flexibility and resilience to cope with the differences in practices, guidance, beliefs and behaviours of individual midwives within and between workplaces, was seen as paramount. Conclusion: Broadening the perspective of the individual learner to the complex interplay between all the stakeholders involved with workplace learning is an essential step to move forward in the effort to improve student midwives' learning in the workplace.